Peran Pemerintah Daerah Dalam Pelaksanaan Ibadah Haji Di Gorontalo - Abdul Latif; Fadilah Kadir; Farhan Sukarno Putra; Hadija Inangge (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
The role of local government in facilitating the Hajj pilgrimage in Gorontalo is crucial for the smooth execution of this religious obligation. This research delves into the multifaceted involvement of the local government, examining its policies, logistical support, and coordination efforts. Employing a qualitative case study approach, the study evaluates the effectiveness of government policies, challenges faced during the Hajj execution, and the potential areas for enhancement. Findings reveal the significant contributions made by the Gorontalo local government in providing necessary facilities, yet also uncover challenges such as resource limitations and coordination complexities. Recommendations include improving inter-agency collaboration, enhancing policy responsiveness, and infrastructure development to ensure more efficient and satisfactory Hajj experiences. The study serves as a foundational exploration highlighting the importance of government support for successful Hajj implementation in Gorontalo.